2006
DOI: 10.1521/suli.2006.36.5.569
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behaviors and Personality Structure

Abstract: In this paper we suggest the potential clinical usefulness of two projective tests (Rorschach and Object Relation Technique) and of a clinical interview focused on the pathway to suicide, life events, and major life difficulties to better define subtypes of patients attempting suicide. Thirty-three hospitalized subjects who had attempted suicide in the previous 6 months were examined using an in-depth assessment of the pathway to suicide. The aims of this study were: (1) to compare, within a clinical sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…Although depression was the most common psychopathologic condition in our study as in the other studies (Gould et al, 2001; Ialongo et al, 2002), we were not able to find any comorbid with alcohol and substance addiction or abuse, probably a result of Islamic belief prohibiting the use of alcohol (Lester, 2006). In one fifth of our subjects, Axis II psychopathology (i.e., personality disorders) was present in parallel to previously reported rates (9%–30%) (Grava et al, 2006; Vijayakumar, 2005), with the most common personality disorder—was borderline personality disorder—just as it is in the literature. We found no difference between genders in terms of presence of any comorbid psychopathology, suggesting that comorbid psychopathologies are generally strong determinants of suicidal behavior.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although depression was the most common psychopathologic condition in our study as in the other studies (Gould et al, 2001; Ialongo et al, 2002), we were not able to find any comorbid with alcohol and substance addiction or abuse, probably a result of Islamic belief prohibiting the use of alcohol (Lester, 2006). In one fifth of our subjects, Axis II psychopathology (i.e., personality disorders) was present in parallel to previously reported rates (9%–30%) (Grava et al, 2006; Vijayakumar, 2005), with the most common personality disorder—was borderline personality disorder—just as it is in the literature. We found no difference between genders in terms of presence of any comorbid psychopathology, suggesting that comorbid psychopathologies are generally strong determinants of suicidal behavior.…”
Section: Discussionsupporting
confidence: 87%
“…The difference between with and without repeated suicide attempt/ideation groups in respect to Axis I pathologies was found to be insignificant, but the difference of Axis II was of significance. This may reflect the importance of Axis II pathologies in repeated suicidal attempts; for example, the personality disorders have been related to the suicidal attempts (Grava et al, 2006)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What remains relatively unknown, however, is whether these conditions are correlated with method of suicide, although the one study to date that has examined this question found no relationship [31]. Because depressive disorders are twice as high among suicidal women as men [32], studies of suicide methods should account for the influence of these conditions.…”
Section: Correlates Of Suicide Riskmentioning
confidence: 99%
“…Apenas para se ter um panorama de como o Método de Rorschach tem sido pesquisado nos últimos anos, podemos citar investigação de: pessoas com problemas de alcoolismo e uso de drogas (Schiltz, 2008), comportamento suicida (Grava, Ceroni, Rucci & Scudellari, 2006), retardo mental (Di Nuovo, Buono, Colucci & Pellicciotta, 2004), Transtorno de Pânico (Villemor-Amaral, Franco & Farah, 2008), insônia (Carvalho et al, 2003), Lúpus Eritematoso Sistêmico (Santoantonio, Yazigi & Sato, 2004), portadores de HIV (Fioroni & Figueiredo, 2003). E, ainda, com motoristas infratores que tiveram suspenso o direito de dirigir (Frasson & Souza, 2002), bem como com estudantes de medicina (Rossetto, Skawinski, Coelho, Rossetto Júnior & Bolla, 2000 2 Entende-se aqui como "população não-paciente" pessoas sem histórico de desajuste psicológico ou transtorno psiquiátrico e que estejam em atividade laboral e/ou estudantil, incluindo pessoas em atividades domésticas.…”
unclassified